Addition of amendments to restore a compacted soil under no-tillage system - Barbieri, Rayner Sversut; Gabioud, Emmanuel Adrian; Wilson, Marcelo Germán; Sasal, Maria Carolina; Seehaus, Mariela; García-Tomillo, Aitor; Silva, Tatiane Carla [UNESP]; Montanari, Rafael [UNESP] (Universidade Estadual de Maringa, 2023)
The addition of organic and inorganic amendments can improve soil structure and reduce soil compaction. In this context, this study aimed to evaluate whether the application of amendments reduces penetration resistance (PR) in the short term and describe the spatial variability of PR in the surface horizon of an Aquic Argiudoll under no-tillage in northeast Argentina. Four treatments, consisting of surface applications of 7.5 Mg ha−1 poultry litter (PL), 3.0 Mg ha−1 gypsum (G), the combination of PL+G, and untreated control (T), were arranged in a complete randomized block design with three replications. Two more treatments were added to the experiment 12 months later, consisting of PL reapplications on half of the surface of the PL+G and PL treatments (PL+G+PL and PL+PL, respectively) in a split-plot design with three replications in 4×20-m plots. PR was determined in the field with an Eijkelkamp penetrologger following a 2-m long transect perpendicular to the sowing direction at 10 different spots separated 0.2 m from each other. The spatial variability was quantified for each treatment using semivariograms. The highest PR was observed in the T treatment (1.96 MPa) and the lowest PR in PL+G+PL (0.21 MPa). All treatments showed a high spatial dependence (94.9 to 99.9%). Treatments with PL reapplication (PL+PL and PL+G+PL) showed profiles with lower PR and more homogeneous kriging maps. PL reapplication on PL treatments showed no effects on PR values. However, PL reapplication on the PL+G treatment led to positive effects in all PR ranges. Thus, the PL+G+PL treatment, which had the highest PR values, showed a decrease in PR from 54.17 to 6.65% with the reapplication 12 months later. The addition of organic and inorganic amendments reduced specific compacted soil areas on the surface horizon of an Aquic Argiudoll under no-tillage.
Keywords: gypsum; Mollisol; penetration resistance; poultry litter